Soroprevalência de leptospirose em cavalos com transtornos reprodutivos (Revista de Educação Continuada em Medicina Veterinária e Zootecnia do CRMV-SP, 2019)
Leptospirosis is an important zoonotic-disease of global importance and worldwide distribution that cause reproductive failure (abortions/stillbirths) and uveitis in horses. The horses are susceptible to different f Leptospira spp. serovars, and the prevalence may vary according to region, seasonality, and risk factors.